Surfactant‐free synthesis of poly (styrene‐co‐acrylamide) monodisperse nanoparticles using hybrid flow‐to‐batch chemistry. Issue 9 (11th September 2020) - Antoniv, Marta; Chang, Sehoon; Al‐Jabri, Nouf; Zhu, S. Sherry
Abstract: We have demonstrated a hybrid flow‐to‐batch process for synthesizing monodisperse poly(styrene‐ co ‐acrylamide) nanoparticles via a surfactant‐free emulsion radical polymerization. The flow‐to‐batch synthesized nanoparticles have a smaller average particle size, tighter particle size distribution, higher molecular weight, and lower molecular weight distribution compared to conventionally batch‐synthesized nanoparticles. Our results also indicate that the flow‐to‐batch synthesized nanoparticles have more hydrophilic acrylamide segments on the particle surface than the batch‐synthesized nanoparticles. These results demonstrate that a flow synthesis process can improve the quality of nanoparticles due to the efficient mixing and heat transfer in a flow reactor and simplify the scale up of nanoparticle synthesis in a conventional chemistry lab. Abstract :